Experimental investigation of changes in methane adsorption of bitumen-free Woodford Shale with thermal maturation induced by hydrous pyrolysis. (January 2015) - Hu, Haiyan; Zhang, Tongwei; Wiggins-Camacho, Jaclyn D.; Ellis, Geoffrey S.; Lewan, Michael D.; Zhang, Xiaolong
Abstract: This study quantifies the effects of organic-matter (OM) thermal maturity on methane (CH4 ) sorption, on the basis of five samples that were artificially matured through hydrous pyrolysis achieved by heating samples of immature Woodford Shale under five different time–temperature conditions. CH4 -sorption isotherms at 35 °C, 50 °C, and 65 °C, and pressures up to 14 MPa on dry, solvent-extracted samples of the artificially matured Woodford Shale were measured. The results showed that CH4 -sorption capacity, normalized to TOC, varied with thermal maturity, following1 the trend: maximum oil (367 °C) > oil cracking (400 °C) > maximum bitumen/early oil (333 °C) > early bitumen (300 °C) > immature stage (130 °C). The Langmuir constants for the samples at maximum-oil and oil-cracking stages are larger than the values for the bitumen-forming stages. The total pore volume, determined by N2 physisorption at 77 K, increases with increased maturation: mesopores, 2–50 nm in width, were created during the thermal conversion of organic-matter and a dramatic increase in porosity appeared when maximum-bitumen and maximum-oil generation stages were reached. A linear relationship between thermal maturity and Brunauer–Emmett–Teller (BET) surface area suggests that the observed increase in CH4 -sorption capacity may be the result of mesopores produced during OM conversion. No obvious difference is observed in pore-size distribution and pore volume for samples with pores <2.0 nm with the increase of thermal maturity based on CO2 physisorption at 273 K. The isosteric heat of adsorption and the standard entropy for artificially matured samples ranged from 17.9 kJ mol −1 to 21.9 kJ mol −1 and from −85.4 J mol −1  K −1 to −101.8 J mol −1  K −1, respectively. These values are similar to the values of immature Woodford kerogen concentrate previously observed, but are larger than naturally matured organic-rich shales. High-temperature hydrous pyrolysis might have induced Lewis acid sites on both organic and mineral surfaces, resulting to some extent, in chemical interactions between the adsorption site and the methane C–H bonds. The formation of abundant mesopores (2–50 nm) within organic matter during organic-matter thermal maturation makes a great contribution to the increase in both BET surface area and pore volume, and a significant increase in 2–6 nm pores occurs at maximum-oil-generation and oil-cracking to gas, ultimately controlling the methane-adsorption capacity. Therefore, consideration of pore-size effects and thermal maturity is very important for gas in place (GIP) prediction in organic-rich shales. Highlights: Woodford Shale was heated by pyrolysis to achieve 5 distinct maturation levels. Methane has a higher affinity for thermally mature shale. Abundant 2–50 nm size pores are formed during OM conversion to oil and gas. Strong relation exists between CH4 sorption and pore structure during OM maturation.